Revegetasi untuk Rehabilitasi Lahan Pasca-Tambang Wilayah Operasi PT Pertamina Hulu Rokan, Riau - Edi Rusdiyanto; A. Hadian Pratama Hamzah; Nurhasanah Nurhasanah; Abdillah Lubis (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the impact of mining activities on the environment and evaluate the effectiveness of revegetation processes in restoring ecosystem balance in Indragiri Hulu Regency, Riau Province. Mining activities carried out by PT. Pertamina Hulu Rokan have caused deforestation due to tree cutting for land clearing, contributing to habitat disruption for flora and fauna, declining water quality, and increasing global warming. The research method includes literature review, field observations, and interviews with relevant stakeholders. The revegetation process consists of three main stages: land preparation, planting implementation, and maintenance. Additionally, plant species used in revegetation are selected based on suitable characteristics such as resistance to sunlight exposure, fast growth with low costs, high litter production that decomposes easily, strong root systems, and the ability to form symbiotic relationships with specific microbes. The results indicate that revegetation using a combination of ground cover plants, primary plants, and companion plants can improve post-mining environmental conditions, increase oxygen availability, and aid in global warming prevention. Thus, revegetation serves as an effective strategy in post-mining ecosystem restoration efforts. Keywords: Environment, Post-Mining, Global Warming, Revegetation, Plants